Optical properties of human brain and tumour tissue: An ex vivo study spanning the visible range to beyond the second near‐infrared window. Issue 4 (12th February 2022) - Shapey, Jonathan; Xie, Yijing; Nabavi, Elham; Ebner, Michael; Saeed, Shakeel R.; Kitchen, Neil; Dorward, Neil; Grieve, Joan; McEvoy, Andrew W.; Miserocchi, Anna; Grover, Patrick; Bradford, Robert; et al.
Abstract: Neuro‐oncology surgery would benefit from detailed intraoperative tissue characterization provided by noncontact, contrast‐agent‐free, noninvasive optical imaging methods. In‐depth knowledge of target tissue optical properties across a wide‐wavelength spectrum could inform the design of optical imaging and computational methods to enable robust tissue analysis during surgery. We adapted a dual‐beam integrating sphere to analyse small tissue samples and investigated ex vivo optical properties of five types of human brain tumour (meningioma, pituitary adenoma, schwannoma, low‐ and high‐grade glioma) and nine different types of healthy brain tissue across a wavelength spectrum of 400 to 1800 nm. Fresh and frozen tissue samples were analysed. All tissue types demonstrated similar absorption spectra, but the reduced scattering coefficients of tumours show visible differences in the obtained optical spectrum compared to those of surrounding normal tissue. These results underline the potential of optical imaging technologies for intraoperative tissue characterization. Abstract : In‐depth knowledge of a target tissue's optical properties across a wide‐wavelength spectrum could inform the design of optical imaging and computational methods to enable robust tissue analysis during surgery. We adapted a dual‐beam integrating sphere to analyse small tissue samples and investigated ex vivo optical properties of five types of human brain tumour and nine different types of healthy brain tissue across a wavelength spectrum of 400 to 1800 nm.